5-aminoisoquinoline improves renal function and fibrosis during recovery phase of cisplatin-induced acute kidney injury in rats. Issue 2 (27th April 2018) - Quesada, Andrés; O'Valle, Francisco; Montoro-Molina, Sebastián; Gómez-Morales, Mercedes; Caba-Molina, Mercedes; González, Juan Francisco; de Gracia, María C.; Osuna, Antonio; Vargas, Félix; Wangensteen, Rosemary
Abstract : The aim of the present study is to analyze the effects of 5-aminoisoquinoline (5-AIQ), a poly(ADP-ribose) polymerase-1 (PARP1) inhibitor, over renal dysfunction and fibrosis during recovery phase of cisplatin (CisPt)-induced acute kidney injury (AKI) in rats. Male Wistar rats were distributed in three groups ( n =8 each group): control, CisPt, and CisPt + 5-AIQ. Control and CisPt groups received a subcutaneous injection of either saline or 7 mg/kg CisPt, respectively. CisPt + 5-AIQ group received two intraperitoneal injections of 10 mg/kg 5-AIQ 2 h before and 24 h after CisPt treatment. Thirteen days after the treatment, rats were housed in metabolic cages and 24-h urine collection was made. At day 14, CisPt-treated rats showed increased diuresis, N-acetyl-β-d -glucosaminidase (NAG) excretion, glucosuria and sodium fractional excretion (NaFE), and decreased creatinine clearance (CrCl). 5-AIQ significantly increased CrCl and decreased NAG excretion, glucosuria, and NaFE. In plasma, CisPt increased sodium, urea, and creatinine concentrations, while 5-AIQ treatment decreased these variables to the levels of control group. 5-AIQ completely prevented the body weight loss evoked by CisPt treatment. CisPt also induced an increased renal expression of PAR polymer, α-smooth muscle actin (α-SMA), transforming growth factor-β1 (TGF-β1), and collagen-IV. These variables were decreased in CisPt + 5-AIQ group. Tubular lesions and renal fibrosis were also decreased by 5-AIQ treatment. We conclude that inhibition of PARP1 with 5-AIQ can attenuate long-term nephrotoxic effects associated with the CisPt treatment, preventing renal dysfunction and body weight decrease and ameliorating tubular lesions and collagen deposition.